Impact of regional technology policy on local economic development - Frederic Bougrain (European Regional Science Association (ERSA), 1998)
During the last few years, there has been a wide competition among less favoured regions to attract additional productive capacity. The aim of these policies was to compensate the losses in employment in traditionnal sectors by attracting foreign owned branch plants. However the effectiveness of these policies has been rather limited. Branch plant cannot be considered as autonomous production units. They tend to have a technological strategy defined by their parent firm. Most of the time, this signifies the absence of in-house R&D and limited contacts with local markets. It is likely that this situation prevents the transfer of technology into the local economy. Moreover firms with headquarters located overseas may also disinvest from their host country and move to another region to benefit from other financial assistances. In recent years, new initiatives emerged. Policy makers are trying to build local business networks instead of attracting existing plants. One of the aim of this research paper is to explain the issue facing public authorities which sponsorize these initiatives. We will draw upon case studies made of projects which were coordinated by an association located in Bourges (city located in the Centre of France). The program has been launched in 1996 to alleviate the problems of transition from military to civil industries. The goals of the association are threefold : - For many years firms activities have been dedicated to military related markets. To avoid the closures of their establishments, locally based companies that have been dependent on stable and protective military contracts, need to find new markets. The first aim of the association is to identify these new potential markets. - The second is to foster local inter-firm collaboration. - The third is to establish an information center. We will try to identify barriers to collaboration and reasons which explain firms interest in local networks (Some of the firms which have joined the programme are affiliated companies). Before this empirical study, we will describe the notion of networks and discuss their role in innovation.
Keywords: 330